Math goes to the movies - Polster, Burkard 1965-; Ross, Marty 1959- (Johns Hopkins Univ. Press, 2012)
Mel Gibson teaching Euclidean geometry, Meg Ryan and Tim Robbins acting out Zeno's paradox, Michael Jackson proving in three different ways that 7 x 13 = 28. These are just a few of the intriguing mathematical snippets that occur in hundreds of movies. Burkard Polster and Marty Ross have pored through the cinematic calculus and here offer a thorough and entertaining survey of the quirky, fun, and beautiful mathematics to be found on the big screen. 'Math Goes to the Movies' is based on the authors' own collection of more than 700 mathematical movies and their many years using movie clips to inject moments of fun into their courses. With more than 200 illustrations, many of them screenshots from the movies themselves, this book provides an inviting way to explore math, featuring such movies as: 'Good Will Hunting'; 'A Beautiful Mind'; 'Stand and Deliver'; 'Pi'; 'Die Hard''; and, 'The Mirror Has Two Faces'